Clinic management system with notification using GSM modem - Ahmad Kamal, Mat Zain (2012)
Clinic is an organization that is responsible in providing a health medication and treatment for all types of peoples. Surely,everyday there are people that need to use the clinic services.But how can clinic provide a faster and efficient services if they are still using the traditional method on their daily operation?The traditional method means the customers need to fill in their detail in registration form manually and the information will only keep in files.After the registration,the files will be place in the rack and this will cause problems like taking a longer time to retrieve the information, make mistakes during writing or misplaced the files.